Strengthening the Monitoring and Reporting Policy of DPRD's Aspirational Programs (Pokir) Based on An Integrated Information System in North Gorontalo Regency - Latif M.Pasi (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2026)
The Main Thoughts (Pokir) of the Regional House of Representatives (DPRD) serve as a strategic instrument in regional development planning. However, the management of Pokir in North Gorontalo Regency faces accountability issues in the post-budgeting phase due to a weak monitoring and reporting system. This policy paper aims to formulate a policy to strengthen an integrated and performance-based monitoring system for Pokir. Employing a descriptive qualitative approach with a case study of the 2022-2025 period, data were obtained from documents of the DPRD Secretariat, Bappeda, BPKAD, and literature reviews. The analysis was conducted through problem identification using the USG (Urgency, Seriousness, Growth) method, formulation of three policy alternatives, and evaluation using criteria of effectiveness, efficiency, long-term impact, regulatory compliance, and stakeholder acceptance. The results indicate that out of 2,130 Pokir proposals, more than 80% were untraceable in terms of realization. The main root cause is the absence of an integrated information system, leading to scattered realization data across respective Regional Apparatus Organizations (OPD). Among the three alternatives analyzed, the Development of a Digital Monitoring Information System for Pokir was selected as the priority policy with the highest score (4.40). This policy will be implemented through optimizing the e-Monep application of Gorontalo Province, equipped with tagging features, unique Tracking IDs, a real-time dashboard, as well as regulatory strengthening and the establishment of a cross-institutional Pokir Coordination Team. This policy is expected to enhance the accountability, transparency, and effectiveness of Pokir expenditure, strengthen regional legislative governance, and support synchronization with the Regional Government Information System (SIPD) and data preparation for the Corruption Eradication Commission's Monitoring Center for Prevention (MCP).